Adhérer ou résister : la relation ambivalente des artistes aux musées - Glicenstein, Jérôme (Muséologies)

(untitled) (Association Québécoise de Promotion des Recherches Étudiantes en Muséologie (AQPREM), 2018)
Increasingly, contemporary artists are receiving invitations from museums; and not simply to present works produced elsewhere, but to carry out projects on site designed specifically for the museum. In addition to commissions for conventional in situ installation projects, of the type Daniel Buren has conducted for nearly fifty years, numerous invitations call on artists to introduce a fresh perspective on collections, through presentations that diverge distinctly from typical museum practices. Different approaches can be observed—often revealing a very critical perspective on the museum institution—their common feature being that they are presented as an alternative to the practices of museum professionals, while resulting from a negotiation with them. The carte blanche thus represents a new form of conjoint practice— a duel expressivity—directly linking contemporary creation to its institutionalization, where the relationship between the parties concerned is neither completely visible nor completely equitable.